Curriculum Development of Islamic Religious Education in the Digital Era Transformation - Trianita, Amanda; Silma, Amelia Putri; Ridwan, Ahmad; Mulyawan, Faisal (Journal of Islamic Education and Ethics, 2025)
Information and communication technology development in the last few decades has transformed many aspects of human life, including education. Digital transformation has brought challenge and opportunity to education systems in the world. In Indonesia, Islamic education has a crucial role in building character and morals of the younger generation. The Islamic religious education curriculum is often considered less responsive to the dynamics of technological change. Digital transformation in Islamic education provides many opportunities to increase the efficiency, effectiveness and quality of Islamic education. Some of these opportunities are the use of technology in learning, data management and curriculum development. This research aims to describe curriculum development for Islamic religious education in the digital era. The study used a library research method, in this case author collected various literatures related to the topic of discussion, namely the Islamic Education curriculum in the digital era. The research aims to evaluate the effectiveness of implementing technological approaches in curriculum development. The results of this study indicate that technology integration in Islamic education can improve the quality of learning, if implemented with careful planning and proper support. The research also identified some challenges, such as the digital gap and lack of teacher training, and social cultural influence. The long-term goal of this research is to provide policy recommendations that can support the development of a more inclusive and effective technology-based curriculum.